ANALISIS CERPEN “HUKUMAN TERBAIK” KARYA DYAH WAHYUNINGSIH: KAJIAN STRUKTURALISME - Puan Annisa Pane; Naima Azmi Hutagalung; Safinatul Hasanah Harahap (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
"Hukuman Terbaik" by Dyah Wahyuningsih is a short story that contains social criticism of the rampant betrayal that begins with a struggle. The purpose of this research is to describe the intrinsic structure and genetic structure of the short story "Hukuman Terbaik" by Dyah Wahyuningsih. This research was conducted using descriptive qualitative research method with the help of structuralism study approach. The findings show that structurally the short story "Hukuman Terbaik" has complete intrinsic elements such as theme, character and characterisation, plot, setting, time setting, social setting, and point of view. Meanwhile, the genetic structure found is such as humanitarian facts and the author's worldview. The human facts in this short story illustrate the social reality between Samiran and other additional characters that build strength in conveying the current state of life of Samiran. The author's worldview focuses on criticism of the reality, according to which the depiction of punishment through dialogue or expressions delivered is ultimately to convey the appropriate punishment for a traitor. Keywords: Short story, structuralism-genetics, betrayal, punishment.